Production of Lignocellulolytic Enzymes and Phenolic Compounds by Lentinus strigosus from the Amazon Using Solid-State Fermentation (SSF) of Guarana (Paullinia cupana) Residue - Campos, Ceci Sales; Santos, Everaldo Silvino Dos; Nascimento, Larissa Batista Dedo Brito; Chevreuil, Larissa Ramos; Costa, Carla Laize dos Santos Cruz; Pessoa, Vitor Alves; Aguiar, Lorena Vieira Bentolila de; Gouvêa, Paula Romenya dos Santos; Oliveira Júnior, Sérgio Dantas de (Applied Biochemistry and Biotechnology, 2022)
The Amazon rainforest has a rich biodiversity, and studies of Basidiomycete fungi that have biomolecules of biotechnological interest are relevant. The use of lignocellulosic biomass in biotechnological processes proposes an alternative use, and also adds value to the material when employed in the bioconversion of agro-industrial waste. In this context, this study evaluate the production of lignocellulolytic enzymes (carboxymethylcellulases (CMCase), xylanase, pectinase, laccase) as well as phenolic compounds and proteases by solid-state fermentation (SSF) using the fungus Lentinus strigosus isolated from Amazon. The guarana (Paullinia cupana) residue was characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). SSF was carried out with 60% humidification of the residue, at 30 °C, for 10 days. The lignocellulosic biomass presented fragmented structures with irregular shapes and porosities, and was mainly constituted by cellulose (19.16%), hemicellulose (32.83%), and lignin (6.06%). During the SSF, significant values of CMCase (0.84 U/g) on the 8th day, xylanase (1.00 U/g) on the 7th day, pectinase (2.19 U/g) on the 6th day, laccase (176.23 U/mL) on the 5th day, phenolic compounds (10.27 μg/mL) on the 1st day, soluble proteins (0.08 mg/mL) on the 5th day, and protease (8.30 U/mL) on the 6th day were observed. In general, the agro-industrial residue used provided promising results as a viable alternative for use as a substrate in biotechnological processes. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Agro-industrial residue; Basidiomycete